2016
DOI: 10.1111/lam.12611
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus haemolyticus as a potential producer of biosurfactants with antimicrobial, anti-adhesive and synergistic properties

Abstract: This work is the first to show the production of biosurfactants by Staphylococcus haemolyticus strains. Extracts showed antimicrobial, anti-adhesive and synergistic properties against a variety of relevant human pathogens, including the producing strains. In addition to the biotechnological potential, biosurfactants produced by Staph. haemolyticus are potentially undescribed virulence determinants in their producing strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…Because S. haemolyticus is one of the most important CoNS and no CRISPRs have been described to the species so far, the multiplex PCR reaction was employed in 59 clinical strains of this species previously shown by our group to be phenotypic and genetically diverse ( Rossi et al, 2016b ). The cas1 gene was amplified in only 3% of the strains (2/59), namely MD03 and MD25.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because S. haemolyticus is one of the most important CoNS and no CRISPRs have been described to the species so far, the multiplex PCR reaction was employed in 59 clinical strains of this species previously shown by our group to be phenotypic and genetically diverse ( Rossi et al, 2016b ). The cas1 gene was amplified in only 3% of the strains (2/59), namely MD03 and MD25.…”
Section: Resultsmentioning
confidence: 99%
“…Both cas1IIF/R and cas1IIIF/R primer pairs were used in a multiplex polymerase chain reaction (PCR) reaction containing 2 U of the GoTaq G2 DNA Polymerase (Promega, United States) in the enzyme buffer, containing 0.2 mM of each dNTP, 0.2 mM of each primer and 0.1 mM of the primer pair 16S rRNAF/R ( Chen et al, 2013 ) as an endogenous control. Screening was performed in 59 clinical strains of Staphylococcus haemolyticus previously analyzed by our group and shown to be phenotypic and genetically diverse ( Barros et al, 2012 ; Rossi et al, 2016b ). Amplification was performed in a T100 Thermal Cycler (BioRad, United States) with the following cycle parameters: initial denaturation at 95°C for 3 min, followed by 30 cycles (95°C for 30 s, 50°C for 1 min, and 72°C for 1 min) and 72°C for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…Rossi et al . () showed that some strains of biosurfactant‐producing Staphylococcus haemolyticus had antimicrobial activity against a range of Gram‐positive and Gram‐negative bacteria and subinhibitory concentrations of the biosurfactant were able to decrease biofilm formation and showed synergistic effects with tetracycline.…”
Section: Antimicrobial and Antifungal Properties Of Biosurfactantsmentioning
confidence: 99%
“…Ghribi and Ellouze-Chaabouni (2011) isolated a biosurfactant-producing strain B. subtilis SPB1 (HQ392822) and identified antimicrobial activity against micro-organisms with multidrug-resistant profiles (Ghribi et al 2012). Rossi et al (2016) showed that some strains of biosurfactant-producing Staphylococcus haemolyticus had antimicrobial activity against a range of Gram-positive and Gram-negative bacteria and subinhibitory concentrations of the biosurfactant were able to decrease biofilm formation and showed synergistic effects with tetracycline.…”
Section: Antimicrobial and Antifungal Properties Of Biosurfactantsmentioning
confidence: 99%
“…38 Soil contaminations with hydrocarbons are widely proven to be persistent in nature, poorly soluble in water, and often associated with toxic and carcinogenic effects. 39 Current soil remediation techniques require basically heavy, expensive equipments, and even display several environmental risks. 40 The low water solubility of hydrocarbons constitutes one of the main problems affecting their biodegradation efficiency.…”
Section: Discussionmentioning
confidence: 99%